Finding Alcatrazes and early Luso-African settlement on Santiago Island, Cape Verde. (8th August 2017) - Evans, Christopher; Sørensen, Marie Louise Stig; Allen, Michael J.; Appleby, Jo; Casimiro, Tania Manuel; French, Charles; Inskip, Sarah; Lima, Jose; Newman, Richard; Richter, Konstantin; Scaife, Rob
Abstract : After the Portuguese discovered the Cape Verde Islands in AD 1456 they divided its main island, Santiago, into two governing captaincies. The founding settlement in the south-west, Cidade Velha, soon became the Islands' capital and a thriving trade centre; in contrast, that in the east, Alcatrazes, only lasted as an official seat from 1484–1516 and is held to have 'failed' (see Richter2015 ).